Using a Fuzzy NSBM Model with Shared Resources and Undesirable Variables for the Assessment of Universal Banking System - Homa Ghasemi; Esmaeil Najafi; Farhad Hosseinzadeh Lotfi; farzad movahedi (مدیریت مهندسی و رایانش نرم)
With regard to the entry of most banks into the competitive environment of universal banking, as a customer-centric approach aiming to provide financial services to customer groups, it is important to assess the performance of the business process in bank branches using this approach. Due to the uncertainty and desirability of some indicators as well as the existence of shared resources in the real environment of modelling, this paper aims to design a network fuzzy data envelopment analysis (DAE) model, with the simultaneous consideration of undesirable variables and shared resources, and its practical use to measure the effectiveness of service delivery process in universal banking. The results indicate how the branches performed in each of the processes of universal banking. The lower mean efficiency of service provision to customers reflects the necessity for the bank to provide a portfolio of products and better credit services. Comparing the performance of branches in terms of each process can play an important role in the adoption of incentive and punitive policies for managers.